FINANCIAL MANAGEMENT OF UPZ INSTITUTIONS IN MAXIMIZE ZAKAT POTENTIAL - Pranoto, Pranoto (Smart Education, 2025)
Abstract: This study aims to analyze the financial management of the Zakat Collection Unit (UPZ) of Pamulang University (UNPAM) in its efforts to maximize the potential of zakat from lecturers and students. Using a qualitative approach with descriptive quantitative elements, this study explores the financial management practices of UPZ, the perceptions of muzakki (lecturers and students) towards transparency and accountability, and the factors that influence their participation in paying zakat through campus institutions. Qualitative data were collected through in-depth interviews with UPZ managers as well as lecturers and students, and document analysis. Descriptive quantitative data were obtained through a questionnaire survey of a sample of lecturers and students to measure the level of awareness, participation, and perception of zakat management. The results of the study indicate a gap between awareness of zakat and the level of participation through UPZ, as well as the need to increase transparency and accountability in financial management to build muzakki trust. Strengthening the financial management system, intensifying socialization regarding the role and programs of UPZ, and evaluating the effectiveness of zakat fund distribution were identified as key factors in maximizing the potential of zakat in the UNPAM environment. This study concludes that effective and reliable financial management is an important foundation for UPZ UNPAM to optimize the collection and utilization of zakat from the campus academic community for the welfare of the community. Keywords: Financial Management, Zakat Collection Unit (UPZ), Zakat Potential, Accountability Abstrak: Penelitian ini bertujuan untuk menganalisis pengelolaan keuangan Unit Penghimpun Zakat (UPZ) Universitas Pamulang (UNPAM) dalam upayanya memaksimalkan potensi zakat yang bersumber dari dosen dan mahasiswa. Dengan menggunakan pendekatan kualitatif dengan unsur deskriptif kuantitatif, penelitian ini mengkaji praktik pengelolaan keuangan UPZ, persepsi muzakki (dosen dan mahasiswa) terhadap transparansi dan akuntabilitas, serta faktor-faktor yang memengaruhi partisipasi mereka dalam membayar zakat melalui lembaga kampus. Data kualitatif dikumpulkan melalui wawancara mendalam dengan pengelola UPZ serta dosen dan mahasiswa, dan analisis dokumen. Data deskriptif kuantitatif diperoleh melalui survei kuesioner terhadap sampel dosen dan mahasiswa untuk mengukur tingkat kesadaran, partisipasi, dan persepsi terhadap pengelolaan zakat. Hasil penelitian menunjukkan adanya kesenjangan antara kesadaran berzakat dengan tingkat partisipasi melalui UPZ, serta perlunya peningkatan transparansi dan akuntabilitas dalam pengelolaan keuangan untuk membangun kepercayaan muzakki. Penguatan sistem pengelolaan keuangan, intensifikasi sosialisasi peran dan program UPZ, serta evaluasi efektivitas penyaluran dana zakat menjadi faktor kunci dalam memaksimalkan potensi zakat di lingkungan UNPAM. Penelitian ini menyimpulkan bahwa pengelolaan keuangan yang efektif dan andal menjadi landasan penting bagi UPZ UNPAM untuk mengoptimalkan penghimpunan dan pendayagunaan zakat dari sivitas akademika kampus demi kesejahteraan masyarakat. Kata Kunci: Manajemen Keuangan, Unit Penghimpun Zakat (UPZ), Potensi Zakat, Akuntabilitas